LEVONORGESTREL-RELEASING INTRAUTERINE SYSTEM IN ADENOMYOSIS; PREDICTORS FOR RESPONSE AND CLINICAL OUTCOME - J Alizzi, Fadia; Khaliq Showman, Hind Abdul; A Fawzi, Hayder (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim is to detect clinical and ultrasonographic characters that predict the response of adenomyosis to levonorgestrel-releasing intrauterine system (LNG-IUS) and to evaluate the clinical efficacy and the time needed to show a response. Methods: A prospective single-arm study conducted in the Obstetrics and Gynaecology Department Al-Yarmouk Teaching Hospital in Baghdad/Iraq from August 2015 to March 2018. Women with symptomatic adenomyosis with age 39 years and above and who completed their families had been enrolled in this study. LNG-IUS was used as a treatment; the outcome measure was to evaluate its effect in improving the symptoms and the time needed to show a clinical response. Multivariate analysis was used to assess the contribution of the clinical and ultrasonographic parameters to the prediction of the response to LNG-IUS. Results: Over the mean duration of follow-up period of the study (22.7Â±9.9 months), there was a significant improvement in menstrual blood loss, dysmenorrhea, and hemoglobin (Hb) with significant decrease in uterine volume (pË‚0.001). The time to show response was as early as 3 months and the first 6 months is the best time to predict failure. Initial menstrual blood loss and Hb were good predictors to show response while uterine volume an excellent one (positive predictive value 80% and negative predictive value 97.2%). Conclusion: Levonorgestrel-releasing intrauterine device is an effective treatment of symptomatic adenomyosis in term of time to response and duration of response. The presenting Hb, menstrual blood loss, and uterine volume are useful predictors of response.